Bawaslu Efforts In Preventing Election Violations To Dealing With Identity Politics In The Post Truth Era - Elsa Kristina Hutapea; Puguh Santoso; Halomoan Freddy Sitinjak Alexandra; Achmed Sukendro; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The role of Bawaslu in seeking supervision in order to prevent election violations for face identity politics. Especially in the development of technology to mass media so public must understand the Post Truth era and not get carried away with false news. The purpose of this study is to find out and analyze Bawaslu in preventing future election violations. This article was formed by researchers by collecting data from various sources, such as journal articles, books, reports and other related sources. Results study this shows that though there are challenges that must be faced by Bawaslu but Bawaslu already has six strategies that are used as guidelines in preventing election violations especially deal with identity politics. Based on Justice's six strategies be prepared and carried out by Bawaslu has put forward the prevention of identity politics and is quite effective and can continue until after the election.